Tumor cell expression of B7-H4 correlates with higher frequencies of tumor-infiltrating APCs and higher CXCL17 expression in human epithelial ovarian cancer. (2nd December 2019) - MacGregor, Heather L.; Garcia-Batres, Carlos; Sayad, Azin; Elia, Andrew; Berman, Hal K.; Toker, Aras; Katz, Sarah Rachel; Shaw, Patricia A.; Clarke, Blaise A.; Crome, Sarah Q.; Robert-Tissot, Celine; Bernardini, Marcus Q.; et al.
ABSTRACT: B7-H4, an immune suppressive member of the B7 family, is highly expressed in a wide variety of human malignancies making it an attractive immunotherapeutic target. However, the association between B7-H4 expression in the tumor microenvironment and the immune infiltrate has not been comprehensively examined. To evaluate the immune tumor microenvironment, we analyzed epithelial ovarian tumors from 28 patients using flow cytometry, immunohistochemistry, functional, and genomic analyses. We determined B7-H4 expression patterns and compared the immune infiltrates of tumors with high and low surface expression of B7-H4. Frequencies and phenotypes of tumor and immune cells were determined using multiple flow cytometry panels. Immunohistochemistry was used to analyze cellular infiltration and location. Publicly available datasets were interrogated to determine intratumoral cytokine and chemokine expression. We found that B7-H4 was predominantly expressed by tumor cells in the epithelial ovarian tumor microenvironment. Surface expression of B7-H4 on tumor cells was correlated with higher levels of infiltrating mature antigen-presenting cells. Further, expression of CXCL17, a monocyte and dendritic cell chemoattractant, correlated strongly with B7-H4 expression. T cells expressed activation markers, but T cells expressing a combination of markers associated with T cell activation/exhaustion phenotype were not prevalent. Overall, our data suggest that B7-H4 is associated with a pro-inflammatory tumor microenvironment.